Secondary hemophagocytic lymphohistiocytosis in a child with Leptospira infection: A case report - Dragana Jevtic; Dragomir Djokic; Danka Redzic; Dragana Aleksic; Miro Parezanovic; Srdjan Pasic (The Turkish Journal of Pediatrics)
Leptospirosis caused by spirochetes of the genus Leptospira in most patients result in very mild illness without jaundice. However, a small portion of patients develop various complications due to the involvement of multiple organ systems. Hemophagocytic lymphohistiocytosis is characterized by prolonged fever, hepatosplenomegaly and cytopenias, hyperferritinemia and hypertriglyceridemias, hyperfibrinogenemia, and hemophagocytosis in bone marrow, lymph nodes, spleen, or liver. Hemophagocytic lymphohistiocytosis associated with leptospirosis is a very rare condition and it should be considered in patients with multiple organ dysfunctions, together with adequate laboratory findings. It can delay the correct diagnosis of leptospirosis and contribute to an adverse outcome. We present a 13-year-old girl with secondary hemophagocytic lymphohistiocytosis caused by leptospira infection and favorable outcome with appropriate antibiotics and corticosteroid therapy.